2019
DOI: 10.3390/su11195254
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Helpfulness of Online Restaurant Reviews Using Different Machine Learning Algorithms: A Case Study of Yelp

Abstract: Helpful online reviews could be utilized to create sustainable marketing strategies in the restaurant industry, which contributes to national sustainable economic development. This study, the main aspects (including food/taste, experience, location, and value) from 294,034 reviews on Yelp.com were extracted empirically using the Latent Dirichlet Allocation (LDA) and positive and negative sentiment were assigned to each extracted aspect. Positive sentiments were associated with food/taste, while negative sentim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 72 publications
0
18
0
1
Order By: Relevance
“…The use Recency, Frequency, and Monetary (RFM) features of review along with textual features improved predictive accuracy of review helpfulness [57]. Several studies have proposed review helpfulness prediction models using different features and a number of machine learning techniques [58]- [61]. These techniques for review helpfulness prediction range from simple regression algorithms to complex neural networks [62]- [64].…”
Section: B Features For Predicting Review Helpfulnessmentioning
confidence: 99%
“…The use Recency, Frequency, and Monetary (RFM) features of review along with textual features improved predictive accuracy of review helpfulness [57]. Several studies have proposed review helpfulness prediction models using different features and a number of machine learning techniques [58]- [61]. These techniques for review helpfulness prediction range from simple regression algorithms to complex neural networks [62]- [64].…”
Section: B Features For Predicting Review Helpfulnessmentioning
confidence: 99%
“…Earlier studies identified determinants of review helpfulness and empirically tested factors that affect review helpfulness using traditional research methods, such as surveys, experimental design and content analysis (Hong et al, 2017). Moreover, prior review helpfulness research separately examined descriptive review features (Hu et al, 2017;Siering et al, 2018), review semantic or review sentiment (Luo and Xu, 2019). Therefore, the current study identified and integrated 11 determining review helpfulness factors considering descriptive review, reviewer and restaurant information, and used a thorough literature review to investigate sentiment semantic features.…”
Section: Hospitality Big Data Analyticsmentioning
confidence: 99%
“…RONW it is defined as profits available to equity shareholders/equity shareholders' funds of corporate i at time t, and ROCE it is defined as earnings before interest and tax (EBIT)/capital employed of corporate i at time t. For its part, α t is the constant, and OR it is measured on a five-point Likert scale, considering the value assigned by customers to the factors of food, service, and value for money [66]. This value is obtained from the TripAdvisor website and takes into account the age of the reviews, considering that previous reviews have less impact than recent ones [67].…”
Section: Model Specificationmentioning
confidence: 99%